2015
DOI: 10.1242/dmm.019646
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility to otitis media in a Splunc1-deficient mouse model

Abstract: Otitis media (inflammation of the middle ear) is one of the most common diseases of early childhood. Susceptibility to otitis is influenced by a number of factors, including the actions of innate immune molecules secreted by the epithelia lining the nasopharynx, middle ear and Eustachian tube. The SPLUNC1 (short palate, lung, nasal epithelial clone 1) protein is a highly abundant secretory product of the mammalian nasal, oral and respiratory mucosa that is thought to play a multifunctional role in host defense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 67 publications
2
23
0
Order By: Relevance
“…Calprotectin, a dimer of S100A8 and S100A9, has also been shown to bind to NETs and is reportedly required for NET antifungal activity[ 52 ], likely making it important in OM. SPLUNC, another abundant protein in the MEEs has been demonstrated to contribute to pulmonary host defense, and its depletion in mice leads to middle ear infection[ 53 , 54 ]. Finally, MUC5B, the predominant mucin in human COM fluid[ 14 ] has also shown to be required for airway defense, with its absence leading to severe middle ear infection in mice[ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calprotectin, a dimer of S100A8 and S100A9, has also been shown to bind to NETs and is reportedly required for NET antifungal activity[ 52 ], likely making it important in OM. SPLUNC, another abundant protein in the MEEs has been demonstrated to contribute to pulmonary host defense, and its depletion in mice leads to middle ear infection[ 53 , 54 ]. Finally, MUC5B, the predominant mucin in human COM fluid[ 14 ] has also shown to be required for airway defense, with its absence leading to severe middle ear infection in mice[ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…BPIFA1 was identified as a candidate for OM in a recent GWAS study (Rye et al . , 2012) and loss of the protein has been implicated in the development of OM in aged mice (Bartlett et al . , 2015).…”
Section: Discussionmentioning
confidence: 99%
“… Rye et al (2012 ) identified significant associations at several loci, including CAPN14 , GALNT14 , BPIFA3 and BPIFA1 , identifying novel candidate genes for further analysis. Interestingly, a mouse model of BPIFA1 was recently shown to demonstrate an increased susceptibility to OM ( Bartlett et al, 2015 ). In a second GWAS study ( Allen et al, 2013 ), a novel susceptibility locus on chromosome 2 was identified, with the relevant SNP lying in the intergenic region between CDCA7 and SP3 .…”
Section: Discussionmentioning
confidence: 99%